Factors influencing antibiotic treatment cost and outcome in critically ill patients: A “real-life” study - Perić, Aneta; Šurbatović, Maja; Vezmar Kovačević, Sandra; Antunović, Mirjana; Veljović, Milić; Djordjević, Dragan; Andjelić, Tamara; Zeba, Snježana; Dobrić, Silva (Vojnosanitetski pregled, 2014)
Background/Aim. Critically ill patients are at very high risk of developing severe infections in intensive care units (ICUs). Procalcitonin (PCT) levels are eleveted in the circulation in patients with bacterial sepsis and PCT might be useful in guiding antibiotic treatment. The aim of this study was to estimate factors influencing patients survival and treatment cost in ICU with special emphasis on the impact of PCT serum levels use in guiding antimicrobial therapy. Methods. The study was conducted from August 2010 to May 2012 in the Intensive Therapy Unit, Clinic of Anesthesiology and Intensive Therapy, Military Medical Academy (MMA), Belgrade, Serbia. All adult critically ill patients with sepsis and/or trauma admitted in the ICU were included in the study. This study included only the cost of antimicrobial therapy in the ICU and the cost for PCT analysis. We used prices valid in the MMA for the year 2012. PCT in serum was measured by homogeneous immunoassay on a Brahms Kryptor analyzer. Results. A total of 102 patients were enrolled. The mean patients age was 55 ± 19 years and 61.8% of patients were male. The mean length of stay (LOS) in the ICU was 12 ± 21 days. There was a statistically significant difference (p < 0.001) between the sepsis and trauma group regarding outcome (higher mortality rate was in the sepsis group, particularly in the patients with peritonitis who were mostly women). The patients younger than 70 years had better chance of survival. LOS, the use of carbapenems and PCT-measurement influenced the cost of therapy in the ICU. Conclusions. The obtained results show that age, the diagnosis and gender were the main predictors of survival of critically ill patients in the ICU. The cost of ICU stay was dependent on LOS, use of carbapenems and PCT-measurement although the influence of these three factors on the outcome in the patients did not reach a statistical significance.
Keywords: critical illness; sepsis; anti-bacterial agents; cost and cost analysis; biological markers